Māori Political Representation: A Case for Change - Mahuta, Robert (Maori Representation in Parliament, 1982)
Keywords: mana motuhake; māori electorates; māori seats; population; voting

Tracking Patterns of Tribal Identification in the New Zealand Census, 1991 to 2006 - Kukutai, Tahu; Rarere, Moana (New Zealand Population Review, 2013)
Keywords: census; identification; iwi; population

Census 2018 and Implications for Māori - Kukutai, Tahu; Cormack, Donna (New Zealand Population Review, 2018)
The population census is a universal tool of governance but has come under increasing pressure as governments look to reduce costs, gain efficiencies and counter declining response rates. In Aotearoa New Zealand, the census transformation strategy has a short-term focus on modernising the census and a long-term vision of a fully administrative census. The digital-first 2018 Census was an ambitious step towards modernisation but there are growing concerns that it may fail to deliver high-quality data, particularly for Māori and iwi. This research note considers the implications of lower response rates and reflects on the steps that might be taken to retain the trust and confidence of Māori in the census, including possibilities for Māori data governance across the official statistics system.
Keywords: census; data collection; governance; methodology; population; population studies; sovereignty; transformation